Pengaruh penambahan kacang merah dan ketan hitam terhadap sifat sensori dan gizi minuman berbasis jamur tiram dan wijen hitam[[The effect of the addition of red beans and black glutinous rice on the sensory and nutritional properties of oyster mushroom and black sesame-based drinks] - Anisa Yustiana; Siti Nurdjanah; Samsu Udayana Nurdin; Murhadi Murhadi; Dewi Sartika (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2022)
One example of a plant-based product is mixed grain-based milk. Mixing various types of grains such as red beans, black glutinous rice, black sesame, and oyster mushrooms is expected to complement the nutritional content and improve the sensory properties of the final product. This research was aimed to determine the effect of the proportion of red beans and black glutinous rice on the mixture of grains and oyster mushrooms on the sensory quality of mixed grain milk and find the best proportion of red beans and black glutinous rice in the mixture of grains and oyster mushrooms that produce plant-based milk with the best sensory quality. This research was conducted in a Randomized Complete Block Design (RCBD) with a single treatment in the form of a comparison of red beans, and black glutinous rice consisting of 6 formulations with 4 replications. Parameters observed were sensory properties (aroma, taste and aftertaste). The sample with the best sensory properties was further analyzed proximate content and amino acid profile. The results showed that addition of red beans and black glutinous rice to plant-based milk on oyster mushrooms and black sesame affected sensory qualities (taste, aroma, and aftertaste). The best treatment was the proportion of 60:30 with a taste score of 7.49 (tends to be savory sweet), an aroma score of 7.73 (tends to be pleasant), an aftertaste score of 7.11 (tends to be normal); a moisture content of 85.29%; a protein content of 1.72%; fat content 0.88%; carbohydrates 11.77%; ash 0.34%; and 61.88 kcal of calories per 100 mL.